Characterization of digestate composting stability using fluorescence EEM spectroscopy combining with PARAFAC. Issue 5 (May 2019) - Huang, Jing; Han, Lujia; Huang, Guangqun
A laboratory scale experiment of digestate composting was carried out using a reactor system. In this study, conventional physicochemical and biological analyses were carried out and fluorescence excitation-emission matrix (EEM) spectroscopy combined with parallel factor analysis (PARAFAC) was used to assess the maturity and stability during digestate composting. A four-component model was obtained and three components, i.e. fulvic-like (C1 and C3), protein-like (C2), and humic-like (C4) components, were identified. Furthermore, the ratios of each two components were calculated and the relationships with other parameters were established using Pearson correlation analysis. The results showed that the main humification process during digestate composting was the accumulation of fulvic-like substances and that secondary formation occurred at the late stage of digestate composting. Moreover, the EEM–PARAFAC technique could be used as a sensitive and efficient tool for assessing the dynamic changes of digestate composting. The ratio C4/(C1 + C3) is the most suitable indicator in evaluating the stability of digestate composting.